Henry Bradshaw's Correspondence on Incunabula with J.W. Holtrop and M.F.A.G. Campbell : Volume I. The Correspondence 1864-1884 - Hellinga, Lotte,; Wytze, (European History and Culture - Book Archive pre-2000., 1978)
Valuable correspondence illustrating the birth of the modern method of incunabula studies, known as the Bradshaw-Proctor method. I. The Corrrespondence 1864-1884 (100 Letters) II. Commentary by W. & L. Hellinga The print edition is available as a set of two volumes (9789061949602). See Less